Glimpses of the dilemmas and paradoxes of public administration training in Bangladesh - Waheeduzzaman, Mohammad (Asian Studies, 2025)
The main purpose of this paper is to appraise the relevance, adequacy and usefulness of various training programs of BPATC for better public sector management in Bangladesh. The core training programs of BPATC include the Foundation Training Course (FTC) for the new recruits of the Civil Service, the Advanced Course on Administration and Development (ACAD) for the mid-level civil servants, and the Senior Staff Course (SSF) for the senior-level officers. A sense of optimism was expressed in 1984 that BPATC would become a center of professional excellence' which would be capable of inspiring creativity and innovation in civil service training and professional development for better public sector management. Yet there are those critics who suggest that the creation of BPATC has essentially led to the centralization of civil service training delivery system without any adequate reference to the improvement of the training process and the outcomes of training. Since its formation, BPATC has essentially remained stuck with the "old baggage" that had been inherited or adapted from the abolished training institutions in the form of institutional structures, objectives, trainers, training programs, curricula, and methods of, and approaches to, training. Indeed, the stagnant state of the inappropriate design, implementation and evaluation of PAT programs has essentially remained myopic, episodic, and often meaningless. In view of such a circumstance, the crucial question is whether or not BPATC has risen from the "ashes" of the now-defunct civil service training institutions. It is also a legitimate pursuit to examine whether or not the establishment of BPATC has improved the process and outcomes of training for better public sector management. It is time to ask whether or not the BPATC is adequately prepared and staffed to competently design and effectively implement job relevant and useful training programs for various types and levels of civil servants of Bangladesh.